High frequency of TTK mutations in microsatellite-unstable colorectal cancer and evaluation of their effect on spindle assembly checkpoint - Niittymaki I; Gylfe A; Laine L; Laakso M; Lehtonen HJ; Kondelin J; Tolvanen J; Nousiainen K; Pouwels J; Jarvinen H; Nuorva K; Mecklin JP; et al. (OXFORD UNIV PRESS, 2022)
Frameshift mutations frequently accumulate in microsatellite-unstable colorectal cancers (MSI CRCs) typically leading to downregulation of the target genes due to nonsense-mediated messenger RNA decay. However, frameshift mutations that occur in the 3' end of the coding regions can escape decay, which has largely been ignored in previous works. In this study, we characterized nonsense-mediated decay-escaping frameshift mutations in MSI CRC in an unbiased, genome wide manner. Combining bioinformatic search with expression profiling, we identified genes that were predicted to escape decay after a deletion in a microsatellite repeat. These repeats, located in 258 genes, were initially sequenced in 30 MSI CRC samples. The mitotic checkpoint kinase TTK was found to harbor decay-escaping heterozygous mutations in exon 22 in 59% (105/179) of MSI CRCs, which is notably more than previously reported. Additional novel deletions were found in exon 5, raising the mutation frequency to 66%. The exon 22 of TTK contains an A(9)-G(4)-A(7) locus, in which the most common mutation was a mononucleotide deletion in the A(9) (c.2560delA). When compared with identical non-coding repeats, TTK was found to be mutated significantly more often than expected without selective advantage. Since TTK inhibition is known to induce override of the mitotic spindle assembly checkpoint (SAC), we challenged mutated cancer cells with the microtubule-stabilizing drug paclitaxel. No evidence of checkpoint weakening was observed. As a conclusion, heterozygous TTK mutations occur at a high frequency in MSI CRCs. Unexpectedly, the plausible selective advantage in tumourigenesis does not appear to be related to SAC.